2021
DOI: 10.21873/anticanres.14910
|View full text |Cite
|
Sign up to set email alerts
|

Nondysplastic Crypts in Fission in Nonpolypoid Adenomas and in the Adjacent Mucosa Support Field Cancerization in the Colon

Abstract: Background/Aim: We recently noticed in nonpolypoid adenomas (NPA) and the adjacent normal mucosa, nondysplastic crypts in symmetric and asymmetric fission (NDCSAF). Patients and Methods: All NDCSAF found in 80 small NPA and in the adjacent mucosa were registered. Results: A total of 178 NDCSAF (mean, 2.2) were found: 12 (6.7%) interspersed between adenomatous glands, 36 (20.2%) partially replaced by dysplastic epithelium, and 130 (73%) underneath the adenomatous tissue. Of the 61 cases with normal mucosa adjac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…The progressive accumulation of genetic mutations and DNA methylation changes in normal tissue around tumors lead to the development and progression of adenomas, which might become adenocarcinomas. Such alterations are a result of field cancerization[ 28 ]. Studies have demonstrated that the aberrant methylation of cancer-related genes could serve as epigenetic markers for CRC risk owing to the field of susceptibility[ 29 ], and such findings are consistent with our finding that compared with abnormal DNA methylation in tumor tissue, abnormal DNA methylation in adjacent normal tissue is highly correlated with an unfavorable prognosis after surgical resection.…”
Section: Discussionmentioning
confidence: 99%
“…The progressive accumulation of genetic mutations and DNA methylation changes in normal tissue around tumors lead to the development and progression of adenomas, which might become adenocarcinomas. Such alterations are a result of field cancerization[ 28 ]. Studies have demonstrated that the aberrant methylation of cancer-related genes could serve as epigenetic markers for CRC risk owing to the field of susceptibility[ 29 ], and such findings are consistent with our finding that compared with abnormal DNA methylation in tumor tissue, abnormal DNA methylation in adjacent normal tissue is highly correlated with an unfavorable prognosis after surgical resection.…”
Section: Discussionmentioning
confidence: 99%
“…Inversely, crypt branching was frequently found in the colon mucosa of adult patients having either infectious colitis (24), ulcerative colitis (25), or Crohn's colitis (26). Moreover, crypt branching was also frequent in the nondysplastic colon mucosa adjacent to nonpolypoid adenomas (27). The increase in crypt branching in these instances implies that not only inflammatory insults, but also proximity to mutated neoplastic tissue of nonpolypoid adenomas can unchain crypt replication in the colon mucosa.…”
mentioning
confidence: 99%
“…Following a classical histological description of the normal colon mucosa, it has been axiomatic to describe colon crypts as closely aligned glands in parallel, as "test tubes", vertical to the surface epithelium and the muscularis mucosae (1). However, this description applies only to welloriented, upright crypts, often seen in sections from colectomy specimens (6), or mucosectomies (7). In contrast, endoscopic biopsies in normal donors reveal cross-cut crypts in a horizontal (tangential) plane, displaying ring-shaped cross-cut crypts, similar in outline and diameter (8,9).…”
mentioning
confidence: 99%